Coaching, assessment and teachersâ performance in implementing teaching method of Islamic education of elementary school in Magelang - Solikhah, Nur (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2018)
Related to teacher performance, coaching and assessment are activities continuously carried out by supervisors. This study aims to determine the coaching and assessment conducted by supervisors, and to discover teachersâ performance in implementing teaching method used by Islamic Education teachers of Elementary school in Kota Magelang. Using descriptive qualitative research approach, this study was a field research by involving 3 supervisors and 35 Islamic Education teachers of Elementary School in Kota Magelang. The results of this study indicated: (1) Coaching to teachers of Islamic Education of Elementary School conducted by supervisors has been carried out with appropriate steps and with designing programs in advance which regularly applied through activities of Teachers Working Group (KKG); (2) Assessment to Islamic Education Teachers of Elementary School in Kota Magelang performed by supervisors shall be conducted through regular academic supervision once a semester in accordance with the standards decreed by the government; (3) Islamic Education teachers performance of Elementary School has applied various teaching methods, including Make A Match, Peer Tutor, Knowledge Shop, Problem Solving, Quis Jeopardi, Roll Play, Talking Stick, Mind Map, Number Together, Crossword Puzzle, Interactif Lecture, Jigsaw, and Shortcard.